Good Fences Make Good Neighbours - Maša Poljšak Kus; Urban Kordeš (Ars & Humanitas, 2025)
In this paper we aim to sketch and describe the differences (and some similarities) between the approaches, assumptions and limitations of both natural and phenomenological sciences. We establish the borders of each domain and ask whether consciousness can be found in either, and in what form. In the form of experience, we argue that it can only be found in the domain phenomenological inquiry. Exploration of such a domain requires different set of tools and rules than used in the natural sciences, remaining on its own side of the fence. Phenomenological science needs to embrace the fact that observed phenomena are observer-dependant and focus equally on both the way we observe and what we observe. To develop appropriate methodologies, phenomenological science needs to establish on its own while communicating with the natural sciences in the form of mutual constraints, not prescriptions.